Effects of water exposure on bitumen surface microstructure. (15th March 2017) - Hung, Albert M.; Goodwin, Adrian; Fini, Elham H.
Highlights: The paper introduces a study of surface morphology of bituminous materials. The interaction between water, wax, and surfactants in bitumen was studied. Effects of time and temperature on bitumen surface microstructure were studied. AFM imaging revealed topological evolution of the bitumen with water exposure. Water exposure led to appearance of "nano-bumps" on bitumen surface. Abstract: In applications such as asphalt pavement and roofing shingles, bituminous binder not only binds aggregate structure together but also acts as a waterproof sealant. However, moisture can still diffuse into the binder over time, reducing binder adhesion to aggregate or causing other changes that increase asphalt susceptibility to further water damage. Accordingly, this paper investigates the effects of water exposure at elevated temperature or extended duration on bituminous asphalt binder. Atomic force microscopy (AFM) images of bitumen samples exposed to water at ambient temperature showed "nano-bumps" appearing on characteristic "bee" structures on the bitumen surface, and Fourier transform infrared spectroscopy (FTIR) showed an enrichment of polar compounds at the surface due to water exposure. The nano-bumps are hypothesized to be para phase resin absorbing water and seeping up from underneath the "bee" structure through pinhole defects. At elevated temperature under water, the chemical and structural evolution accelerated, and new "aqueous peri phase" features appeared on the surface that were similar to but independent of the original "bee" structures. The results are important for furthering understanding of the aging process in bitumen under environmental exposure and the relation between composition and performance properties.